Alternatif Penyelesaian Sengketa Antara Perawat dan Pasien dalam Kasus Penanganan Bayi Prematur - Dewiwaty (Jurnal Hukum Lex Generalis, 2021)
Everyone on this earth wants to be healthy. Various efforts are made to be healthy, starting from implementing a good lifestyle to seeking good health services. The role of a health worker, especially a nurse, is also a driving force in the health sector. Duties and authorities must be obeyed by a nurse in carrying out her profession, but all of that is not free from mistakes or omissions made by a nurse to her patients. For this reason, good faith is needed in resolving disputes encountered while carrying out their profession. A dispute that arises between a nurse and a patient or patient's family should be resolved by mediation without being taken directly to legal channels, for this reason, good communication is needed between the two warring parties. All of this was done so as not to cause prolonged fatigue between the two parties in resolving disputes.